Ancestral Languages of Nepal in the 2021 Census - Regmi, Dan Raj (Nepalese Linguistics, 2024)
This paper classifies 124 ancestral languages focusing on language maintenance and shift; and sheds lights on outcome of enumeration of such languages and its implications to language policy implementation in Nepal. In 2021 census, 47 Indo-Aryan and 72 Sino-Tibetan languages were recorded by 78.3% and 21.4% people as ancestral languages, languages, including respectively. major Such languages, including major languages, belonging to different family groups and subgroups, demonstrate pitiable language maintains. This paper classifies 124 ancestral languages focusing on language maintenance and shift; and sheds lights on outcome of enumeration of such languages and its implications to language policy implementation in Nepal. In 2021 census, 47 Indo-Aryan and 72 Sino-Tibetan languages were recorded by 78.3% and 21.4% people as ancestral languages, languages, including respectively. major Such languages,